Altered self-reported resting state mediates the effects of Mindfulness-Based Stress Reduction on mental health: a longitudinal path model analysis within a community-based randomized trial with 6-months follow-up - Lise Juul; Emilie Hasager Bonde; Lone Overby Fjorback (Frontiers in Psychology, 2023)
BackgroundA large body of randomized controlled trials (RCTs) has shown that mindfulness-based interventions are effective for improving mental health, but research is lacking in regards to the mechanisms of change. We aimed to investigate the mediating effects of self-reported altered resting state of Mindfulness-Based Stress Reduction (MBSR) on mental health, when provided as a universal intervention in a real-life context.MethodsAutoregressive path models with three time points of measurement, and contemporaneous and constant b paths were used in an RCT. The RCT took place in all five geographical regions of Denmark and included 110 schools and 191 schoolteachers. The schools were randomized 1:1 in each geographical region to intervention or a wait-list control group. The intervention was the standardized MBSR. Data were collected at baseline and after 3 and 6  months. The outcomes were perceived stress, measured by Cohen’s Perceived Stress Scale (PSS), symptoms of anxiety and depression, measured by Hopkins Symptom Check List-5 (SCL-5), and well-being measured by WHO-5 Well-being Index (WHO-5). The mediator was resting state measured by the Amsterdam Resting State Questionnaire (ARSQ).ResultsStatistically significant mediated effects of altered ARSQ-subscales scores for Discontinuity of Mind, Planning, and Comfort were found for the MBSR effect on all outcomes; PSS, SCL-5 and WHO-5. Furthermore, statistically significant mediated effects of altered sleepiness subscale score of the effects on PSS and SCL-5 of MBSR were found. No statistically significant mediating effects of the subscales Theory of Mind, Self and Somatic Awareness for the MBSR intervention effect were found.ConclusionThe results support that the MBSR program can alter self-reported resting state, towards less mind wandering and more comfort, measured by the ARSQ, and that this may explain some of the mechanisms regarding the effectiveness of MBSR on mental health at 6 months, when provided as a universal intervention. The study provides insight into an active ingredient of how MBSR may improve mental health and well-being. It supports the suggestions that mindfulness meditation may be a sustainable way of training the mental health.Clinical trial registration:ClinicalTrials.gov, identifier NCT03886363.